AN OVERVIEW OF KEY SAFETY CONCERNS AND SUSTAINABILITY OF CNG RETROFITTED VEHICLES IN NIGERIA - Garba, Usman; Musa, Mua'zu (FUDMA JOURNAL OF SCIENCES, 2024)
Compressed natural gas (CNG) is increasingly being advocated and adopted as an alternative fuel for vehicles in Nigeria due to its economic and environmental benefits. However, the retrofitting of vehicles to use CNG has raised safety concerns, particularly in a country like Nigeria where regulatory standards, enforcement, and public awareness may not be fully developed. An assessment of the key safety and sustainability of retrofitted CNG vehicles (CNGVs) focusing on factors such as the quality and durability of conversion kits and tanks, proper installation procedures, CNG storage, and refuelling are considered. While CNG is generally safer than traditional fuels like gasoline and diesel—requiring higher ignition temperatures and presenting less fire risk during leaks, the fear of regulatory oversight, inadequate safety standards, and limited technical expertise in vehicle retrofitting may pose significant challenges. Stronger regulations, public awareness campaigns, and technician training programs are advocated to ensure safe CNGV operations in Nigeria.
Keywords: CNG safety; Vehicle retrofitting; Alternative fuel; Regulatory standards; Risk management